Assessment of volleyball skills as part of the development of young athletes at the Bahana Muda Club - Chandra, Mahesa Dwi; Inzaghi, Usamah Daffa (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
Periodic performance evaluation is the primary foundation for improving athlete performance, especially in sports that demand high technical abilities, such as volleyball. Data-based evaluation is an important instrument for objectively identifying the strengths and weaknesses of athletes, as well as the basis for formulating targeted training programs. This community service program aims to evaluate volleyball playing skills by measuring the technical skills of athletes at the Bahana Muda Club in Malang City. This activity involved 20 male athletes who had experience competing in the Provincial Sports Week (Porprov) event and was carried out with a participatory approach. Several skill tests include passing, service, and smash/spike tests. The measurement results showed that most athletes were in the moderate category (40%), followed by the deficient category (30%), and only one athlete occupied the excellent category. These findings indicate that performance gaps between athletes require more individualized and structured training interventions. In addition to producing preliminary data on athlete performance, this activity also benefits coaches’ awareness of the importance of data-based evaluation in coaching. In conclusion, the performance assessment carried out in this service program provides an objective picture of the athlete’s technical readiness. It can become the basis for preparing an adaptive and sustainable training program. Therefore, it is recommended that evaluative activities like this be carried out regularly to monitor progress and ensure the continuity of athlete performance improvement.